Collaborative Trend Analysis Using Web 2.0 Technologies: A Case Study - Kaiser, Iris (International Journal of Distributed Systems and Technologies, 2012)
Through early trend recognition in the business environment and specific processing within the innovation management, companies can achieve long-term market success. A particular challenge is the systematic identification, gathering, structuration and evaluation of trends. Web 2.0 technologies and especially Wikis, which allow several people to maintain and use content simultaneously, are eminently suitable for an efficient process of continuous collection and analysis of relevant market trends. In this paper, trend management processes are introduced and demonstrated how trends can be collected, structured and communicated within the enterprise using a customized wiki. The trend assessment is carried out inter alia on methods of crowd sourcing, resulting in an extensive evaluation basis. In addition, the presented approach includes a visualization of the trends and its assessment for decision support. A case study of global polymer solutions supplier REHAU AG demonstrates the use of the methodology in practice. Copyright © 2012, IGI Global.
WiSo2-Import:2015-09-25:551
Keywords: Collaboration; Innovation Management; Radar; Trend Scouting; Web 2.0; Wiki

E-Based Market Intelligence: Ein Managementinformationssystem zum Markt für energieeffizientes Bauen - Kaiser, Iris (Dr. Kovac, 2012)
WiSo2-Import:2015-10-05:550

Energieeffizientes Bauen: IT-gestützte Marktkenntnis und Markterkenntnis - Kaiser, Iris; Bodendorf, Freimut; Neukirchner, Jörg (Wirtschaftsinformatik & Management, 2011)
WiSo-Import:2015-03-26:3540

Innovation management in enterprises - Collaborative trend analysis using Web 2.0 technologies - Kaiser, Iris; Durst, Michael (Proceedings of the IADIS International Conference - Collaborative Technologies 2011, 2011)
Through early trend recognition in the business environment and their specific processing within the innovation management, companies can achieve long-term market success. A particular challenge is the systematic identification, gathering, structuration and evaluation of trends. Web 2.0 technologies and especially Wikis, which allow several people to maintain and use content simultaneously, are eminently suitable for an efficient process of continuous collection and analysis of relevant market trends. In this paper, trend management processes are introduced and it is demonstrated how trends can be collected, structured and communicated within the enterprise using a customized wiki. The trend assessment is carried out inter alia on methods of crowd sourcing, resulting in an extensive evaluation basis. In addition, the presented approach includes a visualization of the trends and its assessment for decision support. A case study of global polymer solutions supplier REHAU AG demonstrates the use of the methodology in practice. © 2011 IADIS.
WiSo2-Import:2015-10-07:521
Keywords: Collaboration; Innovation management; Radar; Trend scouting; Web 2.0; Wiki

IT-gestützte Marktforschung - Möglichkeiten einer internationalen webbasierten Marktbeobachtung und -analyse des Marktes für energieeffizientes Bauen - Kaiser, Iris (Multikonferenz Wirtschaftsinformatik 2010, 2010)
WiSo2-Import:2015-10-07:472